(untitled) (REGE Revista de Gestão, 2014)
The aim of this article is to identify and analyze strategic resources mobilization as a theoretical perspective to evaluate the internationalization process, searching to contribute beyond the usual interpretation. The purpose was to investigate how the resource articulation developed by an organization can contribute to the internationalization process, ant its influences on the operations and competitiveness. In the empiric field, a qualitative research through a case study was conducted in Vulcabrás/Azaleia company, focusing on the implementation of subsidiaries for selling and distribution in Colombia, Peru and Chile. The main competencies identified and found in this study were: Capacity of Understanding the Market (DAY, 1994; KNIGHT; LIESCH, 2002, WEERAWARDENA, 2003); Capacity of Learning with a Focus on Internal Environment (WEERAWARDENA, 2003); and Networking Capacity (AXELSSON; JOHANSON, 1992; JOHANSON; VAHLNE, 2009; WEERAWARDENA, 2003). The results indicated that the development and adaptation of the three global operations were dependent on the resources mobilization and have been promoting the construction of these skills as articulators of the internationalization process.